PROBLEM WITH MULTIPOINT CONDITIONS FOR SYSTEMS PARABOLIC EQUATIONS OF HIGT ORDER WITH VARIABLECOEFFICIENTS - Симотюк, Михайло Михайлович; Тимків, Іван Романович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The correctness of the problem with multipoint conditions on time variable and Dirichlet type conditions on spatial coordinate for the system parabolic equations of higt order is investigated. The conditions of existence and uniqueness solution of the problem are established. The metrical theorem on evalution from below of small denominators of the problem are proved.